Understanding the situation of bystanders to inform anti-bullying interventions - Cohane, Samantha K.; Schneider, Barry H. (Frontiers in Psychology, 2024)
Bystanders who witness a bully-victim exchange at their school differ from bystanders who witness many incidents of violence in their community, due to the web of mutual relationships that exist within a school setting. Research conducted in many countries has revealed a variety of ways in which peers too often support and encourage bullies, thereby reinforcing the bully’s behavior and further marginalizing their victims. This elucidates the potential benefits of channeling bystanders’ neutrality into opposition to bullying that is beneficial and supportive of victims. This goal has been incorporated into preventive anti-bullying interventions that have been implemented and evaluated. In this paper, we focus on the contention that systematic anti-bullying intervention in schools and communities can affect the stance of bystanders. We pay particular attention to the KiVa program, which was originally developed in Finland but has since been implemented in schools throughout many countries due to promising data regarding its effectiveness as well as its emphasis on the role of bystanders. We discuss the data documenting the effectiveness of preventive school-based anti-bullying programs, considering the proposition that these programs reduce bullying at least partially by improving bystander behavior. Despite ample evidence that KiVa reduces bullying, there is little specific data showing that the effects of KiVa are mediated by improvements in bystander behavior. The paper concludes with speculation about the possibility of a more direct and active mobilization of student mediators and student leaders to influence the behavior of bystanders in their classrooms and schools.